Towards the origin of evidentiality in nakh-daghestanian languages: structural and areal perspectives - Samira Verhees (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This article deals with the grammatical expression of the source of information by means of past tense forms of the verb (so-called “past unwitnessed” forms) in the East Caucasian (Nakh-Dagestanian) languages. These languages are spoken in a relatively small territory in the Northeast Caucasus and partly in Transcaucasia. It is part of a larger area ranging from the Balkans to Central Asia (including the Caucasus), where similar verb forms are found. It is considered probable that these forms arose among diff erent languages spoken in this area as a result of language contact with Turkic languages. For some languages of this area (e.g. Armenian and Georgian), this hypothesis has been confi rmed. For the East Caucasian languages, this question has not been studied yet. This article is the fi rst attempt to make preliminary assessment of the probability of this hypothesis. First of all, the formal characteristics of these forms in the East Caucasian languages are discussed, as well as their genetic and areal distribution among the languages of the family. It is claimed that this distribution is not trivial. Three distinct zones can be distinguished in the East Caucasian area: more grammaticalised forms are common in the northwest, less grammaticalised expressions are characteristic of the central zone, while they are almost absent in the southern part of the region. It remains unclear which specifi c Turkic language from this region could have acted as a source language, and it is not possible at this point to establish the exact ways in which the feature in question was spread through the East Caucasian family. The specifi c distribution outlined in this paper does, however, indicate that Turkic languages have played a role in the distribution of this feature.